2020
DOI: 10.3390/foods9060688
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Stimulates Thermoregulatory Genes in Brown Fat Tissue and Muscle without an Influence on Inguinal White Fat Tissue in a High-Fat Diet-Induced Obese Mouse Model

Abstract: This study was conducted to investigate if taurine supplementation stimulates the induction of thermogenic genes in fat tissues and muscles and decipher the mechanism by which taurine exerts its anti-obesity effect in a mildly obese ICR (CD-1®) mouse model. Three groups of ICR mice were fed a normal chow diet, a high-fat diet (HFD), or HFD supplemented with 2% taurine in drinking water for 28 weeks. The expression profiles of various genes were analyzed by real time PCR in interscapular brown adipose tissue (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
9
1
Order By: Relevance
“…As this metabolite enhances energy expenditure (35), the finding goes in accordance with the larger fat depots in this group. Although taurine promotes thermogenesis in the BAT and muscle, it does not have the same effect in WAT (72), which was also not observed in the present study. In fact, taurine supplementation was shown to prevent obesity in female mice after 18 weeks of high-fat feeding (36).…”
Section: Discussioncontrasting
confidence: 70%
“…As this metabolite enhances energy expenditure (35), the finding goes in accordance with the larger fat depots in this group. Although taurine promotes thermogenesis in the BAT and muscle, it does not have the same effect in WAT (72), which was also not observed in the present study. In fact, taurine supplementation was shown to prevent obesity in female mice after 18 weeks of high-fat feeding (36).…”
Section: Discussioncontrasting
confidence: 70%
“…Moreover, the levels of taurine in freeze-dried protein from cod, pangasius and chicken were 4.8, 2.6 and 0.6 mg/g ( Table 1 ). The recent notion that taurine may lead to increased energy expenditure and activation of UCP1 [ 10 ] prompted us to investigate the appearance of iBAT in mice fed cod, pangasius and chicken. The brown phenotype was, however, not apparent in any mice and large fat droplets were observed in all groups ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…It is uncertain, however, whether WAT or BAT is involved. Kim et al reported that inclusion of 2% taurine in the drinking water increased expression of thermoregulatory genes in BAT, but not WAT [ 10 ], whereas Guo et al demonstrated that taurine supplementation induced browning of iWAT accompanied with significantly elevated expression of Ucp1 , Ppargc1a and other thermogenic genes [ 60 ]. Here, we did not observe an increased expression of neither Ucp1 nor Ppargc1a , in either BAT or WAT from cod-fed animals, but we cannot exclude the possibility that taurine contributes to the anti-obesogenic properties in the cod-fed mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant [1,17,[52][53][54] Membrane stabilisation [55][56][57] Mitochondrial integrity maintenance [11,13,[58][59][60][61] Vitagene activation [1,[62][63][64][65] Bile acid conjugation [66][67][68][69][70] Ca homeostasis [13,[71][72][73] FA metabolism/oxidation [74][75][76] Energy metabolism [77][78][79] Osmoregulation [13,80,81] Thermoregulation [82][83][84] Detoxification [85][86][87] Neuroprotection [71,[88][89][90][91] Anti-inflammatory [11,[92]…”
Section: Recent Referencesmentioning
confidence: 99%